GENERETOR CURRENTS UNDER SHORT CIRCUITS IN ELECTRIC PROPULSION SYSTEM EQUIPMENT - Mikhalichenko, P. E. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2012)
In the article, a mathematical model of a DC electric propulsion system of the Ukrainian railways is introduced for a short-circuit condition in the traction network and, as its result, generetor current initiation in electric rolling stock. For control of generetor currents and their negative effect, the author suggests automatic field damper application on the rolling stock.